2023
DOI: 10.1002/fsn3.3359
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nutrition education in enhancing knowledge and attitude of pupils on choice of school mid‐day meal in Ibadan, Nigeria

Abstract: Children's food choices affect their nutritional health, development, and well‐being. In Nigeria, school lunch is generally unregulated; the food menu is usually at the discretion of individual vendors forcing pupils to make unsupervised food choices. This study examined the effectiveness of 6‐week nutrition education in enhancing pupils' knowledge and attitude on the school mid‐day meal choices in Ibadan, Nigeria. A pre‐test/post‐test, quasi‐experimental study was conducted with 100 pupils in 4th and 5th grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Guided by the results from previous studies ( 12 , 30 ), curricula for school-aged students were drafted for a DPNEP. A consultative approach was used to synthesize the knowledge of a group of diverse experts through discussion.…”
Section: Results To Date/assessment Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Guided by the results from previous studies ( 12 , 30 ), curricula for school-aged students were drafted for a DPNEP. A consultative approach was used to synthesize the knowledge of a group of diverse experts through discussion.…”
Section: Results To Date/assessment Processmentioning
confidence: 99%
“…Moreover, they are not faced with the challenge of preparing for secondary school; therefore, targeting this group could encourage implementation in practice. Previous studies ( 30 , 48 ) have demonstrated that the inclusion of 30 min of nutritional education per week in elementary school schedules is effective in improving healthy eating behavior; thus, it is important to provide nutrition education that integrates disaster preparedness into the formal education system to develop children’s abilities and preparedness for disasters. This will improve children’s understanding of nutrition in daily life and during disasters and provide opportunities for them to share what they have learned with their families, thereby promoting family and community understanding.…”
Section: Discussion On the Practical Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In families of stunting individuals with 38.9% do not have health insurance. The definition of income, according to Adeoya, Akinwusi and Nagatomi (2023), is the income of the entire family members calculated in one month. The amount of income will be related to the use of health services.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of wasting, food price inflation had little impact on a child's development (weight for height). Nutrition and evaluation of nutritional status among children under the age of 5 have received a lot of attention in developing nations like Nigeria (Adeoya et al, 2023 ; Nkonde et al, 2021 ), but nutrition among women has received less consideration and examination. Furthermore, the awareness of food price and its impacts on body mass index among women is low and there is the misperception that food price does not affect nutrition outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%